The Damara sheep : an appraisal of its reproductive performance and potential - Schoombee, Cornelius Johan Albertus (Stellenbosch : Stellenbosch University, 2018)
Thesis (M.Sc. in Animal Science) -- University of Stellenbosch, 1998.